Carvacrol improves cognitive dysfunction by decreasing amyloid-β accumulation and regulating neuroinflammation in ovariectomized renovascular hypertensive rats - ERTAŞ, BÜŞRA (My University, 2024)
Hypertension contributes to both the development and progression of brain damage and cognitive dysfunction in the postmenopausal period in women. Carvacrol (CAR), which can easily cross the blood-brain barrier, exhibits neuroprotective properties due to its antioxidant, anti-inflammatory, and anti-apoptotic effects. In the present study, we have examined the effect of CAR treatment on learning-memory impairment in a post-menopausal hypertensive rat model that was induced by ovariectomy following two-kidney, one-clip renovascular hypertension surgery. From the third week after the establishment of renovascular hypertension in ovariectomized rats, CAR (40 mg/kg) was administered once daily for consecutive 7 weeks by gastric gavage. Systolic blood pressure was estimated by the tail-cuff method once a week. At the end of the study, cognitive functions were evaluated with behavioral tests and also neurochemical changes were measured in serum, cortex, and hippocampus by ELISA test. Blood pressure was decreased with CAR treatment in hypertensive rats. Serum estrogen levels decreased in ovariectomized rats and did not change with CAR treatment. CAR demonstrated beneficial effects on learning and memory tests as determined by increased recognition index, the number of platforms crossed, and time spent in the target quadrant. Due to CAR treatment, there was a marked reduction in the hippocampal and cortex amyloid-β, osteopontin, interleukin-6 and tumor necrosis factor-alpha levels, and acetylcholinesterase activity, while an increment in neprilysin and interleukin-10 levels was found. In conclusion, since CAR suppressed amyloid-β deposition and neuroinflammation in ovariectomized-hypertensive rats, it is thought that it may be protective against memory disorders in postmenopausal hypertensive women. Keywords Carvacrol, Hypertension, Postmenopause, Amyloid-β, Neuroinflammation, Cognitive impairment
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (Life); Farmakoloji Ve Toksikoloji; Farmakoloji Ve Eczacılık; Life Sciences (Life); Pharmacology & Toxicology; Pharmacology & Pharmacy; Farmakoloji; Pharmacology; Amyloid-β; Carvacrol; Cognitive impairment; Hypertension; Neuroinflammation; Postmenopause